Produção e caracterização de filmes finos recobertos com albumina e fibronectina - Silva, Denise Aparecida Tallarico da (Universidade Federal de São Carlos, 2012)
Properties related to the increase in the durability of the implants and reliable and faster biological responses are commonly exploited in different areas of scientific research. The physical and chemical phenomena that occur on the surface of the bone/implant interface determine the biological responses following the implantation of biomaterials and therefore are critical to the effectiveness of the process of osseointegration. This work involved the growth and characterization of nanostructured thin films produced by sputtering of TiO2, ZrO2, Nb2O5, and Zr/Ti/Nb on Si(111) and stainless steel substrates, and their subsequent coating with proteins (bovine serum albumin - BSA and fibronectin - Fn). The characterization techniques employed were: X-ray-photoelectron spectroscopy - XPS, atomic force microscopy AFM, time-of-flight secondary ion mass spectrometry - ToF-SIMS, energy-dispersive X-ray spectroscopy - EDS, and nanoindentation. All films showed low surface roughness, nanostructured s grains, and low elastic moduli. The protein adsorption analysis demonstrated that the Zr/Ti/Nb film deposited onto steel and heat-treated had the highest affinity for albumin and that TiO2 film had the highest affinity for fibronectin. All films demonstrated to be suitable for use as protective coating for metallic orthopedic implants
Keywords: Titânio; Biomateriais; Filmes finos; Proteínas; Zircônio; Nióbio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA